Práticas de difusão e comunicação de acervos sonoros no MIS-RJ : caminhos para um guia - Dias, Pedro Henrique Santos (2023)
This qualitative exploratory research seeks to structure paths for the dissemination of the MIS-RJ sound collection based on its use for the production and qualification of the content destined for digital environment. Through readings from a historical perspective and a theoretical framework based on museology, social memory and creative economy, it lists possible elements that highlight the role of museums in the contemporary world and the new challenges presented to guard institutions in their communication practices. As a field of experimentation, it reports the work of digitization and the most recent communication and dissemination practices carried out in the last 10 years at MIS-RJ. Along with this experience report, semi-structured interviews were also carried out with 4 other institutions. Using content analysis of these interviews, it was possible to point out categories that emerged from the discussion, being understood as possible axes for the construction of a cultural product that expands the formats of use of MIS-RJ's sound collection. They are: Document technical treatment, Communication practices and Museum policy. In this way, it proposes debating a new look at the dissemination of its sound collection, through which it can be able action policies in the current economic and cultural situation for this and other Brazilian institutions of memory